Efficient Technology for Increasing the Efficiency of Small Scale Capture Fisheries Effort, A Review - Adi Susanto (JURNAL PERIKANAN DAN KELAUTAN, 2011)
The potential fisheries in Indonesia has been used by the community in various ways and scale. Most of the existing fishing effort is a small-scale business with a variety of problems faced including the increase in cost, aquatic environment degradation, decline in the catch as well as problems related to non-targeted fishes. In order to overcome these problems required an Appropriate Technology so that the small-scale fishing enterprises can continue to evolve. Types of appropriate technology or so called TTG, which can be adopted to improve the efficiency of small-scale fishing enterprises, namely: attractor squid, deep-sea traps, and fish meat bone separator